Stretching and Exploiting Thresholds for High-Order War - Connable, Ben; Campbell, Jason H.; Madden, Dan (RAND Corporation, 2023)
Since 9/11, Russia, China, and Iran have successfully exploited or stretched U.S. thresholds for high-order war in order to further their strategic ends and, in the process, undermine U.S. interests. Each of these countries has made expert use of some combination of measures short of war to enact its strategies. This report describes those measures and how these nation-states use them and explains why U.S. notions of thresholds might be outdated.